KHANPUR CANOLA (KN-279); NEWLY APPROVED LONG SILIQUED, BOLD SEEDED, HIGH YIELDING WITH IMPROVED QUALITY, DOUBLE ZERO (00) VARITY OF RAPESEED (Brassica Napus L.) - AHMAD, I; SALEEM, S; GHAZALI, HMZU; MASOOD, SA; JAMIL, M; FAHEEM, U; HUSSAIN, F (Biological and Clinical Sciences Research Journal, 2022)
The promising variety “Khanpur Canola” (KN-279) is an outcome of hybridization (KN-120 × Shiralli) durong 2006-07 and chosen through Pedigree strategy for determination. Homozygous descendants were built in 2014-15 for yield assessment. Its exhibition was assessed in on station, micro yield preliminaries and national level Uniform Rapeseed Yield Preliminary trials. It has demonstrated its worth in all yield preliminaries and its exhibition is superior to every one of the current developed assortments. Its greatest yield of 3400 kg/ha was accomplished in NURYT 2018-19. It produced 22% higher yield in micro yield trials against standard variety during 2016-17. It surpassed the check (Faisal Canola) with 21% better return in National Uniform Rapeseed Yield trials in 2017-18. Similarly, in NURYT 2018-19 KN-279 gave 19% higher seed yield than the check hybrid Hyola 401.Khanpur canola is a striking cultivated new endorsed assortment having great qualities and reasonable for palatable oil creation. It has the erucic acid; 4.04 % and Glucosinolates; 17.20 µ mole/g oil and it gives 40-46 % eatable oil content on extraction. Agronomic examinations uncovered that this assortment needs no unique creation innovation bundle and fit in a superior manner with the current agronomic practices. The competitor assortment additionally showed most extreme aphid resistance when contrasted with the actually agronomic practices. It is reasonable for climatic states of both inundated and rain-fed region of the Punjab.